2020
DOI: 10.37635/jnalsu.27(1).2020.189-200
|View full text |Cite
|
Sign up to set email alerts
|

Human Life and Health as an Object of Environmental Law in the Globalised World

Abstract: The article examines the issues of legal protection of human life and health in the latest globalisation processes, which have covered all spheres of political, economic, financial, social, geographical and cultural life and are becoming a basic factor of humanity on the planet. These processes set new trends in the ecological development of the state, redefine the problems of environmental security due to the changing nature of the challenges and threats facing humanity. The unfavourable state of the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The data also showed that, with the exception of 2017 and 2019, there were more accidents that occurred at the facilities (56.0%) than accidents outside the facilities (44.0%). This can be explained by the fact that outside the premises there are only selective collection activities and maintenance of selective disposal; all other activities are performed at the company premises (Yoon et al, 2013;Getman, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The data also showed that, with the exception of 2017 and 2019, there were more accidents that occurred at the facilities (56.0%) than accidents outside the facilities (44.0%). This can be explained by the fact that outside the premises there are only selective collection activities and maintenance of selective disposal; all other activities are performed at the company premises (Yoon et al, 2013;Getman, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The similarity of the results lies in emphasizing the importance of understanding the haram and halal in Islam and their impact on Muslims' behavior. There may be differences in approaches to the examination of these concepts, their interpretation, and their relationship to other aspects of Islamic theology and law (Getman, 2020).…”
Section: -17mentioning
confidence: 99%
“…Works of scientists who study and analyze modern issues of our topic form the theoretical basis of our research "Scientific and methodological aspects of solid biofuel production processes in compliance with labor protection and environmental safety measures". These scientists include Aadi Moolam et al (2016), Yeremenko et al (2019), Wang et al (2021, Getman (2020) and Kuznietsova et al (2020) to name but few. Within the framework of the topic under study, aspects of solid biofuel production processes are analyzed in compliance with labor protection measures that are still relevant today.…”
Section: Introductionmentioning
confidence: 99%